The prevalence and management of obstetric fistula among women of reproductive age in a low-resource setting - Olaniyi Felix Sanni; Michael Olugbamila Dada; Abimbola Oluseyi Ariyo; Aisha Oluwakemi Salami; Olaide Lateef Afelumo; Oluwasola Stephen Ayosanmi; Olaiya Paul Abiodun; Elizabeth Abike Sanni (PAGEPress Publications, 2023)
Obstetric fistula is one of the most significant obstetrical concerns and apparent indications of maternal morbidity in low-resource nations. Therefore, the study assessed the prevalence and management of fistula among women of reproductive age (15-49) in low-resource settings. This population-based cross-sectional study was conducted in three local government areas (Jere, Konduga and Maiduguri Municipal City) in Borno State. A structured questionnaire was used to collect data from 484 respondents, and the data were analysed using SPSS version 25.0. The overall prevalence of obstetric fistula was 10.7%. Over 13% of women with seven or more vagina deliveries had a fistula. Likewise, 19% of respondents knew about fistula prevention and treatment services available, and 13.7% of those did not participate in antenatal care services. Furthermore, 48.1% of respondents with a fistula during labour were treated successfully. Almost half (47.9%) who were aware of health facilities around them were successfully treated, same with 46.2% of those living within 1 to 2 km of a health facility, and almost half (49.0%) of those who got married within age 20. The study emphasizes the importance of effective community-level interventions to address obstetric fistula. To achieve this, a comprehensive action plan should be developed, ensuring pregnant women have access to necessary obstetric care services at all healthcare levels. The plan should include preventive measures, timely management of labour complications, and increased awareness of fistula prevention and treatment services. Prioritizing maternal healthcare and empowering women with knowledge and access to services are essential in preventing and managing obstetric fistula.